2023
DOI: 10.1088/1748-9326/acaf10
|View full text |Cite
|
Sign up to set email alerts
|

Windthrow characteristics and their regional association with rainfall, soil, and surface elevation in the Amazon

Abstract: Windthrows (trees uprooted and broken by winds) are common across the Amazon. They range in size from single trees to large gaps that lead to changes in forest dynamics, composition, structure, and carbon balance. Yet, the current understanding of the spatial variability of windthrows is limited. By integrating remote sensing data and geospatial analysis, we present the first study to examine the occurrence, area, and direction of windthrows and the control that environmental variables exert on them across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 110 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…It is worth noting that this linear relationship has large variance because the area of windthrows may be also driven by other factors such as forest resistance, wind direction, accumulated precipitation, etc. (Negron‐Juarez et al., 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that this linear relationship has large variance because the area of windthrows may be also driven by other factors such as forest resistance, wind direction, accumulated precipitation, etc. (Negron‐Juarez et al., 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Increase in associated extreme precipitation with deep convections were observed in US under global warming , which could increase future tree mortality. It is worth noting that there is a significant spread in the linear relationship in Figure 1b, and regional variation caused by species and function traits (Aleixo et al, 2019), soil condition, and surface elevation (Negron-Juarez et al, 2023) can be important factors also affect the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…We used the Purity Pixel Index spectral toolkit ([81], Figure S8) that relied on a wellestablished and reliable method that has been extensively used [1,14,16,17] to select the purest pixels from all images (e.g., areas where all trees were downed versus unaffected old-growth forest) to acquire the most accurate/representative endmembers of interest [27]. Finally, we conducted a SMA to compute fraction images of GV, NPV, and SHD [73].…”
Section: Spectral Mixture Analysis and Remote Sensing Estimates Of Wi...mentioning
confidence: 99%
“…These studies demonstrated that windthrows affect a large portion of the Amazon and occur with a range of intensities and sizes. The Central and Northwestern Amazon regions concentrate the highest incidence of large-scale (>30 ha) events [13,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation